2022
DOI: 10.13057/biodiv/d231235
|View full text |Cite
|
Sign up to set email alerts
|

The screening of probiotic lactic acid bacteria from honey of stingless bee from West Sumatra, Indonesia and using as starter culture

Abstract: Abstract. Melia S, Aritonang SN, Juliyarsi I, Kurnia YF, Rusdimansyah, Hernita VO. 2022. The screening of probiotic lactic acid bacteria from honey of stingless bee from West Sumatra, Indonesia and using as starter culture. Biodiversitas 23: 6379-6385. This study aimed to isolate probiotic lactic acid bacteria (LAB) from stingless bee honey (Galo-galo) and apply it as a starter culture. This research used stingless bee honey (Galo-galo) from west Sumatra, Indonesia. There are 6 types of honey bees, namely Tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…The important role of honey in human health is related to its antimicrobial, anti-inflammatory, and antioxidant activities [8,9]. Melia et al [10] reported antimicrobial activity against several types of pathogenic bacteria in stingless bee honey originating from West Sumatra. Interestingly, honey is gradually gaining popularity as a source of alternative medicines [11] and continues to increase honey consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The important role of honey in human health is related to its antimicrobial, anti-inflammatory, and antioxidant activities [8,9]. Melia et al [10] reported antimicrobial activity against several types of pathogenic bacteria in stingless bee honey originating from West Sumatra. Interestingly, honey is gradually gaining popularity as a source of alternative medicines [11] and continues to increase honey consumption.…”
Section: Introductionmentioning
confidence: 99%
“…One of the bacteria categorized as probiotics is Lactobacillus plantarum SN13T, which was isolated from Tetrigona binghami species stingless bees (galo-galo). A gram-positive, catalase-negative, creamy white bacterium with both homo-and heterofermentative fermentative types is L. plantarum SN13T isolate [4]. The production of fermented milk starter uses the L. plantarum SN13T bacterial culture.…”
Section: Introductionmentioning
confidence: 99%
“…In dadih from different regions (Batusangkar, Alahan Panjang, Padang Panjang, and Agam), there are various types of microorganisms such as Lactococcus, Lactobacillus, Leuconostoc, Klebsiella, Chryseobacterium, Enterococcus, Acetobacter, Acinetobacter, Bifidobacterium, Raoultella, Serratia, Corynebacterium, Staphylococcus, Stenotrophomonas, Frateuria, and others that are unclassified [6] (Fatdillah, 2021). In West Sumatra, there are several functional foods that have the potential to be probiotics, such as Tetrigona binghami stingless honey (galo-galo) with a type of bacteria, namely Lactobacillus plantarum SN13T [7]. Apart from that, there is also tempoyak, which is made from fermented durian fruit with the BAL strain, namely Lactobacillus fermentum CAU6337 [8].…”
Section: Introductionmentioning
confidence: 99%